GOVERNMENT PROGRAM IMPACT ANALYSIS ON EMPOWERMENT OF COASTAL WOMEN TOWARD ENHANCING THEIR FAMILY INCOMES IN THE CITY OF MANADO - Rondonuwu, Deyne (Graduate Program of Sam Ratulangi University, 2013)
The research was conducted in the city of Manado which has received independent direct assistance (Bantuan Langsung Mandiri) from government in 2008 through the coastal women's groups (3 groups) at 3 sub-districts, such as Bunaken Island, East Malalayang I, and Tumumpa II, which aimed to analyze the impact of government support to the activities of coastal women toward enhancing their family incomes. Descriptive method was applied using survey and interview techniques. The data used are primary and secondary data. The data were analyzed by using the formula of the proportion of the income of coastal women. The number of samples was 30; the data was analyzed before getting the assistance (> 2008), after the assistance (2009-2011), and in the period of 2012-2013. The results showed that the total family income increased (30.20-46.21%) after receiving the assistance, in period of 2012-2013 was decreased to 37.36%. This was due to lack of knowledge and skills in the use of coastal women's group capital and lack of technical personnel in assisting the groups. So, the impact of government assistance in the form of independent direct assistance in 2008 was not give any result in enhancing the family income in 2013, since the assistance was not used in a sustainable manner and lack of supervision from technical personnels© Penelitian ini dilakukan di Wilayah Pesisir Kota Manado yang telah menerima Bantuan Langsung Mandiri (BLM) dari pemerintah pada Tahun 2008, melalui 3 kelompok perempuan pesisir, yaitu: Kelurahan Bunaken Kepulauan, Kelurahan Malalayang I Timur, dan Kelurahan Tumumpa II. Penelitian bertujuan untuk menganalisis dampak bantuan tersebut terhadap kegiatan perempuan pesisir dalam meningkatkan pendapatan keluarga. Metode yang digunakan adalah metode deskriptif menggunakan teknik survei dan wawancara. Data yang digunakan adalah data primer dan sekunder. Data dianalisis menggunakan rumus proporsi pendapatan perempuan pesisir. Sampel yang diambil adalah sebanyak 30; data yang dianalisis adalah periode sebelum menerima bantuan BLM (>2008), sesudah mendapatkan bantuan BLM (2009-20011), dan periode Tahun 2012-2013. Hasil penelitian menunjukkan bahwa, secara total, terjadi peningkatan pendapatan keluarga (30,20-46,21%) setelah menerimah bantuan; periode Tahun 2012-2013 menurun menjadi 37,36 %. Hal ini disebabkan oleh kurangnya pengetahuan dan ketrampilan kelompok perempuan pesisir dalam penggunaan modal, serta kurangnya tenaga teknis dalam mendampingi kelompok perempuan pesisir . Sehingga pada tahun 2008, bantuan pemerintah tersebut tidak berdampak pada peningkatan pendapatan keluarga masyarakat pesisir pada tahun 2013, karena pemberian bantuan tersebut tidak dilakukan secara berkelanjutan dan kurangnya pengawasan oleh tenaga teknis©